Prevalence of Non-psychiatric Comorbidities in Pre-symptomatic and Symptomatic Huntington's Disease Gene Carriers in Poland - Zielonka, Daniel; Witkowski, Grzegorz; Puch, Elzbieta A.; Lesniczak, Marta; Mazur-Michalek, Iwona; Isalan, Mark; Mielcarek, Michal (Frontiers in Medicine, 2020)
Huntington’s disease (HD) is monogenic neurodegenerative disorder caused by CAG expansions within the Huntingtin gene (Htt); it has a prevalence of 1 in 10,000 worldwide and is invariably fatal. Typically, healthy individuals have fewer than 35 CAG repeats, while the CAG expansions range from 36 to ~200 in HD patients. The hallmark of HD is neurodegeneration, especially in the striatal nuclei, basal ganglia and cerebral cortex, leading to neurological symptoms that involve motor, cognitive and psychiatric events. However, HD is a complex disorder that may also affect peripheral organs, so it is possible that HD patients could be affected by comorbidities. Hence, we investigated the prevalence of comorbid conditions in HD patients (pre-symptomatic and symptomatic groups) and compared the frequency of those conditions to a control group. Our groups represent 65% of HD gene carriers registered in Poland. We identified 8 clusters of comorbid conditions in both HD groups, namely: musculoskeletal, allergies, cardiovascular, neurological, gastrointestinal, thyroid, psychiatric and ophthalmologic. We found that HD patients have a significantly higher percentage of co-existing conditions in comparison to the control group. Among the 8 clusters of diseases, musculoskeletal, psychiatric and cardiovascular events were significantly more frequent in both pre- and symptomatic HD patients, while neurological and gastrointestinal clusters showed significantly higher occurrence in the HD symptomatic group. A greater recognition of comorbidity in HD might help to better understand health outcomes and improve clinical management.